A Practical Method for Calculating Soil Mixing Wall Retaining Structure by Means of a "Simple Beam Method". (25th January 2023) - Shi, Huwei; Wang, Zhongkai; Huang, Chang; Shi, Huxiong; Wang, Cuiying
Abstract : SMW is the abbreviation of soil mixing wall. H-type steel, also known as the new cement mixing pile wall, is inserted into the cement pile, which combines the bearing load with the impervious water retaining, and has the two functions of stress and impervious retaining wall of the supporting structure. In the design of conventional foundation pit engineering, the active Earth pressure calculated by Rankine's theory is not consistent with the engineering practice because the soil behind the retaining structure has not reached the limit equilibrium state. The embedded depth and the horizontal supporting force of the retaining structure are usually calculated with the equivalent beam method, but the method is complicated. Taking the supporting structure of a foundation pit called "soil mixing wall retaining wall and bolt" as a case, in this paper, the lateral pressure is used to calculate the active Earth pressure at any depth, and the "simple beam method" is used to calculate the embedded depth, the horizontal supporting force, and the internal force of the SMW continuous wall, which intends to find out the first and second supporting points as the pivots of the "simple beam method" under the most unfavorable conditions. When the first pivot is used as the supporting point of the "simple beam method, " the soil pressure is ignored because it is within the critical depth of the Rankine active Earth pressure; while the second pivot is used as the supporting point of the "simple beam method, " the forces on it are balanced to the torque of the second pivot, only considering the moment balance of the active and passive Earth pressure on the isolation body under the second pivot point. The results are in good agreement with the results of the equivalent beam method and the measured values, and they are much closer to the measured values, which provides a practical method for designing SMW retaining structures.